Seismic behavior of RC building with and without buckling restrained braces / Daniel Rumbi Teruna - Teruna, Daniel Rumbi (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2019)
Nonlinear analysis for evaluating seismic performance of building under seismic excitation requires nonlinear properties of any component that are quantified by strength and deformation capacities. The nonlinear behavior of beams and column components are modeled in the form of plastic hinges as described in ASCE41-13 [1] guideline. This document provides the hinge rotation capacity for several ranges of detailing assumption. Buckling restrained braces (BRB) can be modeled as a link element with force-deformation behavior through Wen’s plasticity model. This paper evaluates possible differences of seismic performance of six-story reinforced concrete moment resisting frame with conforming and non-conforming plastic hinge rotation, with and without BRB in placed. The nonlinear static analysis is performed to obtain capacity curve using inverted triangular load pattern as described in ASCE7-10 [2]. The behaviors of investigating frames are discussed and evaluated by means of capacity curves and plastic hinge formation mechanism. Moreover, nonlinear time history analysis is carried out to investigate the effect of BRB properties on the seismic behavior of building model subjected to selected ground motion records. Furthermore, response parameters of building model are presented and compared in the form of base shear, story displacement, and story drift.